PENGARUH KARAKTERISTIK PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Fanny Octavia; Umar Issa Zubaidi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to examine the factors that influence earnings management in non-financial companies. These factors are financial performance, firm’s size, leverage, board of directors, auditor’s size, share issuance activity, and firm’s age. The population of this study was selected by using the purposive sampling method, with a total of 480 obersevations data from 160 non-financial companies listed in Indonesia Stock Exchange from 2018-2020. Those 480 observations data were anaylzed using multiple regression analysis. The results of this study show that financial performance have a positive influence on earnings management, while auditor’s size have a negative influence on earnings management. Other independent variables such as firm’s size, leverage, board of directors, share issuance activity, and firm’s age do not have influence on earnings management.